The Pattern of Maxillofacial Trauma in Children and Adolescents: A 3-Year Retrospective Study: Maxillofacial Trauma in Children and Adolescents - Çulha, Emre; Sabak, Mustafa; Nahırcı, Mikail (Vojnosanitetski pregled, 2025)
Background/Aim: Understanding the epidemiological aspects associated with maxillofacial traumas is necessary for the development of effective preventive and protective strategies. The aim of this study was to analyze the epidemiology and pattern of maxillofacial trauma in patients aged >18 presenting to an emergency department.Methods: Clinical data from individuals aged 0–18 with maxillofacial injuries during 3 years were evaluated. Data pertaining to epidemiological aspects such as injury etiology, age, gender, trauma, and bone fracture type were obtained. Statistical analyses included descriptive, χ2, and logistic regression analyses.Results: Of the 418 patients, 74.64% were male, with a mean age of 8.5± 5.58 years. Of all, 205 cases were of bone fractures, 32.54% of which were cranial bone fractures. About 30.62% of maxillofacial traumas were observed in the 0–3 age group. Further, 65.95% of pediatric maxillofacial trauma cases were caused by falls.Conclusion: The occurrence of maxillofacial trauma was influenced by several factors, including age, gender, and the etiology of the trauma. In pediatric patients, maxillofacial trauma was most prevalent in the 0–3 age group, which also accounted for the highest number of consultation requests. Falls were identified as the primary cause of these injuries, and the current study found that most fractures involved the cranial bones.
Keywords: Etiology of trauma; maxillofacial trauma; children; adolescents